(untitled) (Fiep Bulletin - online, 2015)
This research aims at investigating the glycemic answer to a session of resistance exercises under three food ingestion conditions, as it follows: one session after six hours without any meal (Day1), a second session starting 30 minutes after a snack (Day2) e the third session within six hours without any meal but carbohydrate supplements during trainment (Day3). The sample was constituted by four boys of the age group between 18 and 25 years old who have been practicing body building aiming at hypertrophy. They took a trainment which encompasses ten exercises and had their glycaemic index rated before and after every two exercises which were carried out. The equipment used was a glycosimetre ACCU-CHEK ADVANTAGE from Roche Diagnostics. Data were analysed concerning descriptive estatistics, using the Excell Software 2000. In the situations on Day1 (108.8; 95.6; 104.3; 101.8; 103.5 e 104.3 mg/dl) e Day2 (95.3; 91.3; 93.3; 93.0; 95.3 e 96.3 mg/dl), the average values of the glycaemia decreased while the first rating and increased during the forthcoming ratings which are brought near to resting values. On Day3, the glycaemia went up during the whole exercise, and by the end of the session the values were quite high in relation to resting (88.5; 89.0; 99.3; 112.8; 124.3 e 135.5 mg/dl). In none of the cases the glycaemia reached values which were closer to hypoglycaemia (60 70 mg/dl). In conclusion, the resistance exercise does not call forth high decrease in the glycaemia, probably because the lactato produced during the practise of activities is being used in the glyconeogenesis to maintain the glycaemia with elevated values during the practise of body building. This maintainance of glycaemia may be obstructing the proteolysis process even though the trainment is taken in a fasting situation.